PEMBUATAN ES KRIM KACANG MERAH DENGAN PENAMBAHANVIRGIN COCONUT OIL DAN KUNING TELUR - Sri Winarti; Nana Dyah; Sulistyowati Sulistyowati (BUANA SAINS, 2006)
Ice cream kidney bean was made from ekstrak kidney bean (Phaseolus vulgaris). Extract kidney bean had added value because no cholesterol, hight contain of protein and mineral, had specific flavor and hight contain of dietary fiber. Extract kidney bean low contain of fat (0,645%). When will made ice cream from extract kidney bean, its must to added on fat and emulsifier for produce good emultion. VCO is one of fat wich have functional and egg yolk contain lecitin as good nature emulsifier. The purpose of this research was to found the concentration of VCO and egg yolk for produce good quality of ice cream kidney bean. Experiment design in this research was Random Design with 2 factor, i.e.concentration VCO (6%, 8%, 10%, 12% and 14%) and egg yolk (3%, 4,5% and 6%), each combination twice experiment. The result on this research show that the best treatment was 6% concentration of VCO and 6% egg yolk. This treatment produce ice cream kidney bean with 8,1196% fat contain, 4,595% protein contain, 30,8% total soluble solid, 53,705% overrun, 1,035% stability of emultion and organoleptic teste 6,53 (very like), colour 6,4 (like), texture 6,93 (very like)